Defective Interfering Genomes and the Full-Length Viral Genome Trigger RIG-I After Infection With Vesicular Stomatitis Virus in a Replication Dependent Manner - Linder, Andreas; Bothe, Viktoria; Linder, Nicolas; Schwarzlmueller, Paul; Dahlström, Frank; Bartenhagen, Christoph; Dugas, Martin; Pandey, Dharmendra; Thorn-Seshold, Julia; Boehmer, Daniel F. R.; Koenig, Lars M.; Kobold, Sebastian; et al. (Frontiers in Immunology, 2021)
Replication competent vesicular stomatitis virus (VSV) forms the basis of a vaccine currently tested against Ebola hemorrhagic fever and VSV strains are under development as oncolytic viruses for tumor therapy. Both, the function as live vaccine and as oncolytic virus depend on the ability of VSV strains to induce an adequate amount of interferon type I. It is therefore of great interest to understand in detail how VSV is sensed by the immune system and triggers the interferon response. VSV activates the innate immune system via the cytoplasmic RNA sensor retinoic acid-inducible gene I (RIG-I). In this study we show that VSV needs to replicate to trigger a robust interferon response and that this interferon response requires the production of at least partially double-stranded, 5’-phosphorylated RNA. Analysis of RIG-I-associated RNA by deep sequencing, enzyme digestion and length-fractionation identified a 4719 nt copy-back defective-interfering (DI) genome and the full-length viral genome as main components of the RNA species triggering RIG-I. VSV stocks depleted of DI genomes lost most of their interferon-stimulating activity. The remaining full-length genome and leader-N-read-through sequences were, however, still able to to trigger RIG-I. Awareness for the potential role of DI genomes as trigger of innate immune responses in VSV-based therapeutics will help to standardize DI genome content in virus stocks and may help to purposefully deplete or use DI genomes as natural adjuvants in VSV-based therapeutics.